PENGARUH INISIASI MENYUSU DINI (IMD) TERHADAP KADAR HORMON OKSITOSIN DAN PROSES INVOLUSIO UTERI PADA IBU POST PARTUM RESIKO TINGGI DI RSUD H.PADJONGA DG NGALLE KAB. TAKALAR - Ny. Mantasia (Voice of Midwifery, 2017)
Early Initiation of Breastfeeding (IMD) is the process of feeding the baby immediately after birth for one hour. This study aims to determine the effect of Early Initiation of Breastfeeding Against Oxytocin Hormone Levels And Involusio uteri On Mother Post Partum Resti In Hospital H. Padjonga Dg Ngalle Takalar.This type of research is an analytic observational prospective cohort study design. ie research where data retrieval independent variable (Early Initiation of Breastfeeding) done first, over time new data retrieval performed dependent variable (hormone oxytocin and Involusio uteri) taken by purposive sampling, using primary data. Data analysis by Man Whitney U test.Result showed that early initiation of breastfeeding (IMD) has no effect on the levels of the hormone oxytocin, P = 4.42, early initiation of breastfeeding (IMD) has no effect on uterine involution P = 4.64. Keywords : Early Initiation of Breastfeeding, Hormone Oxytocin, involution uteri